Realitas Akademik Vs idealitas Teori: Evaluasi Pembelajaran Pendidikan Agama Islam di SMA Ibrahimy 2 Sukorejo - Nikmatul Wafiroh; Haifa ratna wiyanti Haifa; Fharadhiesty Abdianty Putri; Fatehatul Hasinah (Civiliza Publishing, Indonesia., 2026)
This study aims to describe and analyze the implementation of Islamic Religious Education (PAI) learning evaluation at SMA Ibrahimy 2 Sukorejo, Situbondo. Using a qualitative descriptive approach, data were gathered through observations, interviews, and documentation. The findings indicate that the school has shifted its evaluation paradigm from traditional categorization (cognitive, affective, psychomotor) towards Formative and Summative Assessments. While differentiated evaluation is successfully implemented such as introducing High Order Thinking Skills (HOTS) for advanced classes challenges like overcrowded classrooms (up to 70 students) and limited technological facilities force teachers to compromise on practical efficiency, such as omitting oral tests. Viewed through an Islamic perspective, these practical adaptations align with the jurisprudence principle of